Myocardial infarction due to thrombotic occlusion despite anticoagulation in Kawasaki disease - a case report - Diana van Stijn; Nikki J. Schoenmaker; R. Nils Planken; Dave R. Koolbergen; Samantha C. Gouw; Taco W. Kuijpers; Nico A. Blom; Irene M. Kuipers (BMC, 2022)
Abstract Background Kawasaki disease (KD) is a pediatric vasculitis. Mainly the coronary arteries become affected due to acute inflammation and formation of coronary artery aneurysms (CAAs) can occur. The larger the CAA, the higher the risk for clinical complications and major adverse cardiac events, as the blood flow changes to vortex or turbulent flow facilitating thrombosis. Such patients may develop life threatening thrombotic coronary artery occlusion and myocardial ischemiaunless anti-platelet and anti-coagulation therapy is timely initiated. Case presentation We present a unique case of a 5-year-old girl with KD associated giant CAAs suffering from myocardial ischemia due to acute progressive thrombus growth despite intensive anticoagulation treatment (acetylsalicylic acid, acenocoumarol and clopidogrel) after 21 months of onset of disease. Thrombus growth continued even after percutaneous coronary intervention (PCI) with thrombolytic treatment and subsequent systemic thrombolysis, finally causing lasting myocardial damage. Acute coronary artery bypass grafting (CABG) was performed, although technically challenging at this very young age. Whereas myocardial infarction was not prevented, follow-up fortunately showed favorable recovery of heart failure. Conclusions Anticoagulation and thrombolysis may be insufficient for treatment of acute coronary syndrome in case of impending thrombotic occlusion of giant coronary aneurysms in KD. Our case demonstrates that a thrombus can still continue to grow despite triple anticoagulation therapy and well-tailored cardiovascular follow-up, which can be most likely attributed to the state of low blood flow inside the aneurysm.